(3CNUQ GdeNJUQGJ aj abg GdEeGe CMeO Hf MfHds - (3eMeO Hf HOQ GdOjf GdHdHGfj GdMfHdj GdOeTbj,J (B1083 (3g` s ((3eOQSI GdMdHi HeOjfI MdH s)
(3ChdgG (B:s
(3hHYO abO SfM HNdOi Cf GNJUQ cJGHi GdeSei HcGa GdeHJOF s
(3BNQgG (B:s
(3hHSJGf Ted GTLGQg hCf COYi CMOgeG UMI GdYbO hGdBNQ aSGOg s
(3hai fgGjJg agQSJs
(3ajg fXGe GdJYbjHI s
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B51 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B100s
Keywords: (3Gdabg GdMfHdjs